CO2 mineral sequestration studies in the ultramafic rocks of northern Pakistan - Tahirkheli, Tazeem; Bilqees, Rubina; Abbas, S. Muntazir; Zakir, Shahida (Journal of Himalayan Earth Sciences, 2012)
One of the greatest threats to environment caused by anthropogenically induced climate change is the production of CO2 as a result of industrialization. How to get rid of, or at least reduce it in the atmosphere to save the environment, is one of the biggest challenges of the day. Under controlled experimental conditions with optimized reaction kinetics, mineral carbonation has considerable potential for the safe disposal of CO2 in the form of environmentally benign carbonates. Pakistan has many major ultramafic complexes with varying thickness and lithologies containing Ca and/or Mg rich silicate minerals, such as pyroxene, olivine, amphibole, serpentine, etc. Our present work is about the mineral carbonation potential of ultramafic rocks of Pakistan, including Chilas and Jijal complexes, Alpuri serpentinites and Dargai ultramafics. The calc-silicates exist in abundance in all of these ultramafic bodies and may act as possible sinks to sequester CO2 in the form of magnesium and calcium carbonates. In this study, approximate amounts of CO2 that can be sequestered in all the ultramafic rocks of Chilas, Jijal, Alpuri and Dargai are estimated using equation formulated by Zevenhoven and Kohlmann, (2001). The approximate covered area of the Chilas complex is 7318 km2, Jijal complex 551 km2, Alpuri serpentinite 16 km2 and that of Dargai ultramafic belt is 153 km2. Taking into consideration the depths, densities and MgO contents, the estimate shows that an ultramafic proportion of 1 million ton (mt.) in the Chilas, Jijal, Dargai, and Alpuri ultramafic can store 01268, 93.79, 47.82 and 1.79 mt of CO2, respectively.